Analgesic Activity, Chemical Profiling and Computational Study on Chrysopogon aciculatus - Zihad, S. M. Neamul Kabir; Bhowmick, Niloy; Uddin, Shaikh Jamal; Sifat, Nazifa; Rahman, Md. Shamim; Rouf, Razina; Islam, Muhammad Torequl; Dev, Shrabanti; Hazni, Hazrina; Aziz, Shahin; Ali, Eunüs S.; Das, Asish K.; et al. (Frontiers in Pharmacology, 2018)
Present study was undertaken to evaluate the analgesic activity of the ethanol extract of Chrysopogon aciculatus. In addition to bioassays in mice, chemical profiling was done by LC-MS and GC-MS to identify phytochemicals, which were further docked on the catalytic site of COX-2 enzymes with a view to suggest the possible role of such phytoconstituents in the observed analgesic activity. Analgesic activity of C. aciculatus was evaluated by acetic acid induced writhing reflex method and hot plate technique. Phytochemical profiling was conducted using liquid chromatography mass spectrometry (LC-MS) and gas chromatography mass spectrometry (GC-MS). In docking studies, homology model of human COX-2 enzyme was prepared using Easy Modeler 4.0 and the identified phytoconstituents were docked using Autodock Vina. Preliminary acute toxicity test of the ethanoli extract of C. aciculatus showed no sign of mortality at the highest dose of 4000 mg/kg. The whole plant extract significantly (p < 0.05) inhibited acetic acid induced writhing in mice at the doses of 500 and 750 mg/kg. The extract delayed the response time in hot plate test in a dose dependent manner. LC-MS analysis of the plant extract revealed the presence of aciculatin, nudaphantin and 5α,8α-epidioxyergosta-6,22-diene-3β-ol. Three compounds namely citronellylisobutyrate; 2,4-dihydroxy-7-methoxy-(2H)-1,4-benzoxazin-3(4H)-one and nudaphantin were identified in the n-hexane fraction by GC-MS. Among these compounds, six were found to be interacting with the binding site for arachidonic acid in COX-2 enzyme. Present study strongly supports the traditional use of C. aciculatus in the management of pain. In conclusion, componuds (tricin, campesterol, gamma oryzanol and citronellyl isobutyrate) showing promising binding affinity in docking studies, along with previously known anti-inflammatory compound aciculatin can be held responsible for the observed activity.